Amos Bronson Alcott: A Case for Romantic Education - Jaime Costa (Universidade do Minho, 2023)
As one of its ideologues, Amos Bronson Alcott constitutes one of the most relevant figures of Transcendentalism or American Romanticism. Confronted with the radical changes of the times he was living in, Alcott will come up with his most daring proposals in the realm of education. The objective of this article is to place Alcott's reformation drive within its philosophical context and to reveal his singular position. Self-awareness, in perspective with nature, constitutes an unavoidable previous step to any educational intent. It is from here that the most useful learning takes place, that which allows for establishing a relationship between the material world and the spiritual world. Alcott identifies the general laws of thought, as series of Maxims, that must at all times guide the instructor. Due to the divine nature of human beings, education will, in the end, be concerned with self-education.